PENGUATAN KPPU MELALUI MODEL SUPERVISI UNTUK MENCEGAH TUMPANG TINDIH KEWENANGAN DALAM PENEGAKAN HUKUM PERSAINGAN USAHA - Alamsyah, Farsya Dalila; Nasco, Muhammad Zayyaan; Situmorang, Christian Immanuel; Kuswoyo, Muhammad Arkan Alfarel (Jurnal Hukum Statuta, 2025)
The establishment of state institutions aims to create a fair and effective legal order. However, over time the complexity of institutional authority often creates overlaps that need to be reviewed to avoid conflicts and clashes between institutions. The Business Competition Supervisory Commission (KPPU) is an example of an institution with authority that clashes with other institutions, such as the judiciary. KPPU has regulatory, administrative, and semi-judicial functions, which can cause overlaps between institutions. KPPU's authority is regulated in Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition, which includes the authority to investigate, examine, and impose administrative sanctions on business actors who violate. The research method used is normative legal research, which examines library materials as well as the reactions and interactions that occur to analyze the application of the law according to applicable regulations without field research. The results of this study conclude: the emergence of urgency to reform the KPPU institution into a model supervision institution in order to create maximum performance and minimize overlapping authority with other institutions